Preparation and Evaluation of Nanostructured Mesalamine Niosomes with Different Concentrations of Non-Ionic Surfactant - Bavaskar, Kedar (International Journal of Pharmaceutical & Biological Archive, 2023)
Introduction: Vesicular drug delivery system is currently the most cutting-edge area of pharmaceutical research. In terms of stability, niosomes are often superior to other vesicular systems like liposomes. Niosomes are a good method for delivering drugs to a particular site of action. Objective: The preparation and evaluation of Mesalamine niosomal dispersion using ether injection and thin film hydration techniques were the goals of this work. The niosomes formulation has tremendous promise and might be used in the future for its clinical implications for a variety of administration methods, making it a more effective formulation for treating diverse illnesses. Mesalamine has potent anti-inflammatory properties. Materials and Methods: In this study, non-ionic surfactants and cholesterol were used at various concentrations to produce niosomes containing dispersion utilizing the thin film hydration technique and the ether injection method. The created formulations were assessed using optical microscopy, zeta potential, in-vitro drug release, and other methods. Results: The ratio 2:1 of span 60 and cholesterol showed better results of the thin film hydration method. Hence, it was optimized as the final vesicle formulation. The results of the Fourier transform infra-red investigation showed that mesalamine did not interact with any of the excipients. As compared to the ether injection method niosomes forming by thin film hydration technique show the best and most promising results. Conclusion: The present study concluded that the thin film hydration technique was an optimized technique for the preparation of mesalamine niosomes than the ether injection method.